2016
DOI: 10.7171/jbt.16-2703-003
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Isomeric Glycopeptide Glycoforms with Hydrophilic Interaction Chromatography (HILIC)

Abstract: The ability to resolve glycans while attached to tryptic peptides would greatly facilitate glycoproteomics, as this would enable site-specific glycan characterization. Peptide/glycopeptide separations are typically performed using reversed-phase liquid chromatography (RPLC), where retention is driven by hydrophobic interaction. As the hydrophilic glycans do not interact significantly with the RPLC stationary phase, it is difficult to resolve glycopeptides that differ only in their glycan structure, even when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 23 publications
(27 reference statements)
5
52
0
Order By: Relevance
“…It was found that both reverse phase and porous graphitized carbon (PGC) chromatography could not separate the individual components. Gratifyingly, hydrophilic interaction chromatography (HILIC) [22], a technique used to separate highly polar compounds [23], showed an incredible ability to fractionate SGP into homogeneous constituents (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that both reverse phase and porous graphitized carbon (PGC) chromatography could not separate the individual components. Gratifyingly, hydrophilic interaction chromatography (HILIC) [22], a technique used to separate highly polar compounds [23], showed an incredible ability to fractionate SGP into homogeneous constituents (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Separation of these isomeric structures is important because changes in the abundance of these isomers can serve as a marker for monitoring of diseases [18]. Huang et al showed HILIC separation of isomeric N -glycan structures, such as sialylated N -glycan isomers differing in α2–3 and α 2–6 linkages, while these glycans remain attached to peptides [19]. Direct analysis of glycopeptides when glycans remain attached on peptides, which has the advantage that the glycosylation can be assigned to specific locations on the protein, is more difficult challenge than glycomic profiling [1923].…”
Section: Introductionmentioning
confidence: 99%
“…LC‐MS/MS is currently considered a great tool for biomolecule identification, enabling simultaneous glycan isomeric separation and structural assignment. Various separation techniques have been developed to resolve glycan isomers at both the glycan and glycopeptide levels . Hydrophilic liquid interaction chromatography (HILIC) coupled with reducing end labeling or derivatization is an excellent approach to separate glycans or glycopeptides .…”
Section: Introductionmentioning
confidence: 99%